Features of the psycho-physiological status of boys in 9-10 years. - Romanenko V.A; Horyakov V.A; Mosenz V.A; Ivanova S.D; Krainyaya N.V; Sokolova V.Y (Kharkov National Pedagogical University, 2012)
The problems of diagnosis of psycho-physiological status of boys in the prepubertal stage of their biological development is considered. The study involved 94 boys aged 9-10 years. They were assessed by parameters of physical development, the functional state of the nervous, cardio-respiratory, muscular and sensory systems and motor fitness, energy and properties of psychodynamics. It is shown that the failure of the approach to assess children's physical health on the grounds of their physical development. Children of this age are characterized by a lag in terms of static lung volume, and vice versa - ahead of age norms in the development of pulmonary ventilation function and resistance to hypoxia. Central hemodynamic parameters vary within age norms. From the observed dominance of neurodynamic mechanisms of excitation and response of advanced type. The established features of the psycho-physiological status, can be used as prognostic indicators in guiding children to sports activities.